2001
DOI: 10.1051/gse:2001120
|View full text |Cite
|
Sign up to set email alerts
|

Detection of quantitative trait loci for growth and fatness in pigs

Abstract: International audienceA quantitative trait locus (QTL) analysis of growth and fatness data from a three-generation experimental cross between Meishan (MS) and Large White (LW) pig breeds is presented. Six boars and 23 F1 sows, the progeny of six LW boars and six MS sows, produced 530 F2 males and 573 F2 females. Nine growth traits, i.e. body weight at birth and at 3, 10, 13, 17 and 22 weeks of age, average daily gain from birth to 3 weeks, from 3 to 10 weeks and from 10 to 22 weeks of age, as well as backfat t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
107
3
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(129 citation statements)
references
References 14 publications
17
107
3
2
Order By: Relevance
“…This may explain the high genetic diversity indices shown by our results and by other European studies [26], [28]. Interestingly, rootstocks show even higher diversity indices even though they are nearly restricted to alluvial zones.…”
Section: Discussionsupporting
confidence: 75%
“…This may explain the high genetic diversity indices shown by our results and by other European studies [26], [28]. Interestingly, rootstocks show even higher diversity indices even though they are nearly restricted to alluvial zones.…”
Section: Discussionsupporting
confidence: 75%
“…A modified version of the CRIMAP 2.4 software ( 66 ), including added utilities provided by X. Liu and M. Grosz (Monsanto, St. Louis, MO), was used for the map construction. Initially, SNPs were assigned to linkage groups (LGs) on the basis of pairwise linkages and the grouping algorithm implemented in the AUTOGROUP option of the program.…”
Section: Methodsmentioning
confidence: 99%
“…European domestic breeds, or Meishan vs. western breeds were extensively used in QTL studies (Andersson et al, 1994; Rothschild et al, 1995, 2007; Janss et al, 1997; Bidanel and Rothschild, 2002; Hu et al, 2007). After the first report on genome-wide scan and detection of QTL for growth, length of small intestine, and fat deposition in pig (Andersson et al, 1994), many QTL studies using F 2 cross populations were performed on growth and fat deposition (Knott et al, 1998; Paszek et al, 1999; Rohrer, 2000; Wada et al, 2000; Bidanel et al, 2001; Malek et al, 2001a; Kim et al, 2005), carcass traits (Andersson-Eklund et al, 1998; Rohrer et al, 1998), and meat quality (de Koning et al, 1999, 2001; Malek et al, 2001b). Recently, several QTL studies on purebreds for meat quality were also reported (Uemoto et al, 2008; Soma et al, 2011).…”
Section: Introductionmentioning
confidence: 99%